Difficult Airway Response Team - What Are the Anesthesiologist’s Roles in Improving the Safety of Airway Management in Outside Operating Theaters? - NAKAGAWA, Masashi (Nihon Rinshō Masui Gakkai shi, 2021)
Worsening respiratory symptoms are the leading cause of rapid response system（RRS）calls from wards. Many patients presenting these symptoms can only be treated with supplemental oxygen, but some require advanced airway management. Airway management in general wards is more difficult than in the operating room because these rooms are small and dark, lack airway management tools, lack support from well-trained persons, and so on. As specialists in airway management, anesthesiologists are responsible for making airway management in these wards safer.At Johns Hopkins hospital, the Difficult Airway Response Team（DART）has been introduced to improve airway management safety in the ward. This is an ideal system for improving safety, but introducing it directly into our own medical system would be difficult. The DART system has three components： operations, safety, and education.Compared to operation center staff, general ward staff lack knowledge of the DAM algorithm and new airway management devices. When anesthesiologists work to secure airways in general wards, this gap in knowledge can make it difficult to manage airways smoothly. Anesthesiologists must provide education to help diminish this gap.